Combining transcatheter arterial embolization with iodized oil containing Apatinib inhibits HCC growth and metastasis - Zhou, Chen; Yao, Qi; Zhang, Hongsen; Guo, Xiaopeng; Liu, Jiacheng; Shi, Qin; Huang, Songjiang; Xiong, Bin (Scientific reports, 2020)
Transcatheter arterial embolization (TAE) plays an important role in clinical liver tumor therapy. However, hypoxia after TAE limit the medium-long term efficacy of TAE. Thus, in our study, we explored the treatment effect and mechanism of combining transcatheter arterial embolization with adopted iodized oil containing Apatinib on suppressing tumor growth and metastasis. We simulated the changing of tumor microenvironment before and after TAE both in vitro and in vivo models. The anti-angiogenic effect of Apatinib was explored by bioassays in human umbilical vein endothelial cells (HUVECs), including cell migration, invasion and apoptosis, tube formation, and wound healing. Further experiments showed that Apatinib inhibited tumor microangiogenesis to achieve the aims of inhibiting tumor growth and recurrence by means of down-regulating the phosphorylation of the RAF-mek-erk, PI3K-akt and P38MAPK pathways. The antitumor growth and anti-angiogenic effect of Apatinib was further validated by the animal experiment. Taken together, we concluded that Apatinib inhibits the angiogenesis and growth of liver cancer by down-regulating the PI3K-akt, RAF-mek-erk and P38MAPK pathways, and has a stronger inhibitory effect in hypoxic environments. Combining TAE with adopted iodized oil containing Apatinib has a stronger inhibitory effect in VX2 liver tumor growth and metastasis, which suggesting such combinations may provide a new target and strategy for interventional therapy of liver cancer.